Effect of ultrasound and storage time on quality attributes of strawberry juice - Tomadoni, Bárbara María (2017)
The aim of this study was to evaluate changes in quality attributes of non-clarified strawberry juice during storage at 5 °C after ultrasonication at 40 kHz for 10 and 30 min in comparison with thermally treated juice at 90 °C for 60 s. Ultrasound treatments maintained color parameters with no significant differences (p <.05) from untreated sample, while thermally treated juice showed lower L* values and higher hue angles than the control. No significant differences in °Brix and total acidity were found between treated and untreated samples, and both parameters remained unchanged throughout storage. Compared to the control, ultrasound treatments showed no significant reductions on day 0 in mesophilic and psychrophilic bacteria, and yeast and molds counts. However, the treatments showed significant decrease in the microbial growth rate through storage time, and significant increase in both polyphenol content and antioxidant activity, compared to control. Practical applications: With today's tendency towards the consumption of nutritious and fresh-like foods, non-thermal treatments are gaining popularity. Among them, ultrasound has become a feasible alternative against traditional thermal treatments. Strawberry products are considered of great nutritional value, because of their high content in antioxidant compounds and vitamin C. In this study, ultrasound was evaluated in strawberry juice through storage time, where significant reductions on microbial growth rate were achieved; meaning that shelf-life of the product was increased compared to control. Furthermore, physicochemical parameters were maintained through storage, and antioxidant capacity and polyphenol content showed a significant increment, which implies that nutritional value of the product was increased by ultrasound treatments. Therefore, sonication is a potential technology that can easily be applied at the fruit juice industry, replacing the traditional thermal treatment which compromises the organoleptical and nutritional quality of the final product.